2019
DOI: 10.7150/ijbs.28422
|View full text |Cite
|
Sign up to set email alerts
|

ING4 suppresses hepatocellular carcinoma via a NF-κB/miR-155/FOXO3a signaling axis

Abstract: The tumor suppressor ING4 has been shown to be reduced in human HCC. The alteration of ING4 contributes to HCC progression. However, its effect in HCC and the potential mechanism is largely unclear. Herein, we found that downregulation of ING4 in HCC tumor tissues was closely associated with cancer staging, tumor size and vascular invasion. Lentivirus-mediated ING4 overexpression significantly inhibited proliferation, migration and invasion, and induced cell cycle G1 phase arrest and apoptosis in MHCC97H human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 60 publications
0
30
0
Order By: Relevance
“…Recent studies have revealed that miRNAs including the miR-200 family regulate the metastasis by enhancing E-cadherin expression and inhibiting EMT [ 25 ]. miR-155 fosters cell migration and invasion in HCC cells via targeting the Ras homolog gene family member A (RhoA) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that miRNAs including the miR-200 family regulate the metastasis by enhancing E-cadherin expression and inhibiting EMT [ 25 ]. miR-155 fosters cell migration and invasion in HCC cells via targeting the Ras homolog gene family member A (RhoA) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that bevacizumab could upregulate ING4, promote cell apoptosis and inhibit cell activity. The increase of ING4 can promote the downstream NF-κB and FoxO3 apoptosis pathways (11,12), so the increase of ING4 is the direct cause of the increase of cell apoptosis rate. In this study, the downregulation of caspase-3, Bax and β-catenin expression and the increase of apoptosis rate in colon cancer cells after knockout of ING4 also prove that ING4 can induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al (11) found that the inhibitory effect of ING4 on melanoma can be realized by activating Fas/caspase-8 apoptosis pathway. Qian et al (12) believed that ING4 can inhibit the growth and metastasis of liver cancer tumor by inhibiting NF-κB and upregulating FoxO3. ING4 plays an important role in colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The prepared 3 µm-thick human lung cancer TMA section was subjected to IHC analysis of SIRT7 using rabbit anti-SIRT7 (1:50) primary antibody and HRP-conjugated anti-rabbit IgG (1:1,000) secondary antibody as previously described ( 31 ). SIRT7 expression level of each specimen was evaluated by a weighted IHC score (0-1, -; 2–3, +; 4–5, ++; and 6–7, +++) ( 31 ). A weighted score of ≥4 (++ or +++) was considered as SIRT7 high expression in a tissue specimen.…”
Section: Methodsmentioning
confidence: 99%